Policies and practices of promise in teacher evaluation: The introduction to the special issue - Audrey Amrein-Beardsley (Arizona State University, 2020)
This introduction to the special issue on "Policies and Practices of Promise in Teacher Evaluation," (1) presents the background and policy context surrounding the ongoing changes in U.S. states' teacher evaluation systems (e.g., the decreased use of value-added models (VAM)s for teacher accountability purposes); (2) summarizes the two commentaries and seven research papers that were peer-reviewed and ultimately selected for inclusion in this special issue; and (3) discussess the relevance of these pieces in terms of each paper's contribution to the general research on this topic and potential to inform educational policy, for the better, after the federal government's passage of the Every Student Succeeds Act (ESSA, 2016).